Green synthesis and photocatalytic insights: A review of zinc oxide nanoparticles in wastewater treatment - Hussain, Rabia Tasaduq; Hossain, Md Sanower; Jun Haslinda, Shariffuddin (Elsevier, 2024)
Embracing sustainable practices like photocatalysis for wastewater management is more crucial than ever. Nanotechnology enhances the effectiveness of photocatalysis, and zinc oxide nanoparticles (ZnONPs) are considered as a promising photocatalyst with large bandgaps and exciton binding energy, which can be synthesized through green approaches. As wastewater treatment with ZnONPs is deemed self-limiting due to various synthesis approaches, a critical evaluation of its purported benefits is necessary. This review summarized current scientific findings based on both unmodified and modified ZnONPs, primarily synthesized using plant sources as reducing and capping agents. The study highlights areas requiring further research, with many plant extracts having been utilized for ZnONP synthesis. Additionally, various dopants, such as carbon derivatives, metal oxides, N-type semiconductors, and metals, have been employed to modify ZnONPs, enhancing their photocatalytic activity. Investigation into biosynthesized ZnONPs, particularly from plant extracts and waste materials, reveals their significant impact on nanoparticle characteristics, including size reduction and bandgap energy control. Secondary metabolites from plant extracts play crucial roles as stabilizing, reducing, and capping agents. The study highlights the superior effectiveness of modified ZnONPs in photocatalysis compared to unmodified counterparts. Integrating renewable, biodegradable resources in bioinspired ZnO-modified photocatalysts opens new opportunities in green technology, offering potential alternatives for water treatment that are cost-effective and environmentally friendly. The utilization of ZnONPs in photocatalysis, particularly when derived from sustainable sources and modified through eco-friendly approaches, presents a promising avenue for addressing global water purification challenges and contributing to a more sustainable future.